ANALISIS KEABSAHAN JUAL BELI PERSPEKTIF EKONOMI ISLAM DAN KUH PERDATA - Arifin, Mohammad; Hilmy Luayyin, Reza; Ayuning Pertiwi, Fia (JSE: Jurnal Sharia Economica, 2024)
Buying and selling is a binding agreement between an individual and another individual to exchange goods or assets according to the agreement of both. Through buying and selling transactions, people can provide assistance to each other, strengthen a sense of brotherhood, and create harmonious relationships between people. The validity of a sale and purchase transaction can be indicated by the acceptance of the agreement and the fulfillment of the contract and the specified conditions, one of which is the obligation to deliver and pay the price. On the other hand, Civil Code Article 1458 states that a sale and purchase can be recognized as valid even though the goods have not been delivered and payment has not been made. The purpose of this study is to identify the validity of a sale according to the views of fiqh muamalah and the Civil Code, as well as to highlight the similarities and differences between the two. The research method used is the comparative descriptive method, which aims to describe the validity of a sale and purchase based on the views of the Civil Code and Islamic law. Data were collected through literature studies with a qualitative approach. The results of this study conclude that, first, the validity of buying and selling in the view of fiqh muamalah is determined by the presence of the seller and buyer, the existence of money and goods being traded, the benefits of the transaction, the condition of the goods that can be delivered, and the knowledge of the seller and buyer about the material, shape, size, and nature of the goods. Second, according to the Civil Code, a sale and purchase is considered valid with an agreement between the parties involved. Third, the similarities found are the importance of consensus or agreement in a sale and purchase transaction, as well as the prohibition of coercion and fraud. In addition, the sale and purchase contract must be carried out by parties who have reached the age of majority, and the goods being traded must be in accordance with applicable regulations. However, there are fundamental differences between the views of muamalah fiqh and the Civil Code. According to Islamic law, a valid sale involves the obligation of delivery and acceptance of the goods by the buyer. On the other hand, the Civil Code permits a sale and purchase in the absence of delivery of goods and payment that has not been made. In Islamic law, the agreement of words alone is not enough, but also requires harmony and meeting certain conditions. Whereas in the Civil Code, the validity of a sale and purchase is achieved only by the occurrence of a contract without considering other aspects